Working with families: A systematic scoping review of family-centred care in universal, community-based maternal, child, and family health services. (June 2021) - Ridgway, Lael; Hackworth, Naomi; Nicholson, Jan M; McKenna, Lisa
Children's long- and short-term health and developmental outcomes can be improved when families are engaged and supported, and inform care planning. Family-centred care (FCC) underpins policy directions for universal, community-based, child and family health services in the early years, although its implementation in this context is poorly understood. This systematic scoping review of the current literature aimed to improve understanding of FCC implementation in maternal, child, and family health universal services. Key databases and grey literature were searched using descriptors of maternal, child, and family health population and context, and FCC concept. Reference checking identified further literature for analysis. Thirteen included papers reported on nine studies from Australia, New Zealand, and the United Kingdom. Limited participant representation of fathers and diverse community members was evident. Deductive thematic analysis identified four areas of FCC demonstrated in this literature: respectful relationships, effective communication to foster shared understanding, flexible and contextualized care, and support for autonomy and agency. The literature demonstrated the interplay between organizational, professional, and recipient factors and their impact on the implementation of FCC. For successful FCC implementation, all these elements should be considered.